2018
DOI: 10.1021/acs.chemrestox.7b00330
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of T-Cell Activation MicroRNAs in Drug-Specific CD4+ T-Cells from Hypersensitive Patients

Abstract: Dysregulation in the expression of microRNAs (miRNAs), single-stranded RNAs which regulate gene expression, has been associated with diseases such as Stevens-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN), although their cellular origin has not been explored. Thus, the focus of this work was to study expression patterns of reported miRNAs involved in T-cell activation following drug-specific stimulation in peripheral blood mononuclear cells (PBMCs) and drug-specific CD4 T-cell clones (TCC) from patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…The involvement of microRNAs (miRNAs) in SJS/TEN has been explored demonstrating that their expression during drug‐specific CD4 + T‐cell activation and cytokine production depends on the drug involved. Carbamazepine was associated with an increase in IFN‐gamma secretion and miR‐18a and miR‐155 upregulation and piperacillin with high miR‐9 and miR‐21 expression in nonproliferating cells …”
Section: New Understanding Of Dhr Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of microRNAs (miRNAs) in SJS/TEN has been explored demonstrating that their expression during drug‐specific CD4 + T‐cell activation and cytokine production depends on the drug involved. Carbamazepine was associated with an increase in IFN‐gamma secretion and miR‐18a and miR‐155 upregulation and piperacillin with high miR‐9 and miR‐21 expression in nonproliferating cells …”
Section: New Understanding Of Dhr Mechanismmentioning
confidence: 99%
“…Carbamazepine was associated with an increase in IFNgamma secretion and miR-18a and miR-155 upregulation and piperacillin with high miR-9 and miR-21 expression in nonproliferating cells. 150 In DRESS, CD4 + T cells show a TH2 pattern with production of IL-5, which is involved in eosinophil activation and recruitment to the affected tissues. 151 In this pathology, it has been also demonstrated the increased type 2 innate lymphoid (ILC2) cells, with a high expression of IL-33 and soluble suppression of tumorigenicity two peptide, important in skin inflammation.…”
Section: T Cell-mediated Reactionsmentioning
confidence: 99%
“…Antigen challenges in DTH influence the profile of miRNAs in human skin samples 133 . This may be associated with a dysregulation of the miRNA expression pattern reported in drug‐specific T cells, which contributed to the severity of the drug‐induced hypersensitivity reaction 134 . Thus, one can speculate that either direct antagonism of upregulated miRNAs by EV‐mediated delivery of anti‐miRNA (anti‐miR) sequences or a reprogramming of APCs to repress the miRNA‐induced effects in T cells would constitute promising alternatives for genetically encoded therapies of hypersensitivities (Figure 1).…”
Section: Antigen‐specific Tolerance In Allergies and Hypersensitivitymentioning
confidence: 99%
“…Additional experiments support the robust linkage between miRNA changes induced by PB and liver cancer in rodent models [ 26 ]. Similarly, cutaneous adverse reactions, such as Stevens-Johnson syndrome (SJS), caused by CBZ are believed to be related to the dysregulation of miRNAs in an immune cell experimental analysis [ 43 ]. This finding will be restated in subsequent chapters.…”
Section: The Epigenetic Effects Of Antiepileptic Drugsmentioning
confidence: 99%
“…CBZ-induced hypersensitivity reactions, such as SJS, are associated with the activation of CD4 + T-cells. A recent study found that miR-18a and miR-155 may be epigenetic factors [ 43 ].…”
Section: Application Of the Epigenetic Effect Of Antiepileptic Drugsmentioning
confidence: 99%